Meeting multiproduct demand with a hybrid inventory replenishment system featuring quality reassurance. (2019) - Chiu, Yuan-Shyi Peter; Chiu, Victoria; Lin, Hong-Dar; Chang, Huei-Hsin
Highlights: A hybrid multiproduct replenishment system featuring quality reassurance is studied. A partial outsourcing option is considered to overcome the capacity constraints. The common fabrication cycle time policy is used for the in-house production. Quality assurance matters including inspection, rework and scrap are considered. A model is built to facilitate managerial planning & controlling decisions. Abstract: Globalization has not only generated immense business opportunities, but also created a very competitive marketplace. To retain competitive advantage, a manufacturer must satisfy a client's multiproduct and quality requirements with limited in-house capacity. An outsourcing strategy can overcome capacity constraints and shorten the fabrication cycle time. This study explores a hybrid multiproduct single-machine inventory replenishment system incorporating an outsourcing plan. The in-house multiproduct fabrication process is under a common cycle time policy. That is, each product receives one replenishment in a common cycle length. All fabricated items are inspected for quality; items with random defects are sorted out as scrap and repairable, and the rework occurs immediately after the regular fabrication. All reworked products that fail the quality reassurance test are scrapped. The quality of outsourcing items is assumed to be guaranteed by the outside provider. Our objective is to determine the optimal common cycle time that minimizes the total relevant cost. An accurate model is constructed to represent the characteristics of the system studied; furthermore, we utilize mathematical analysis to derive the total system costs and apply differential calculus to find the optimal cycle length. A numerical example illustrates the applicability of our result and highlights the effect of variations in outsourcing- and quality-related attributes on the optimal solution, as well as the various performance indicators that facilitate planning and controlling decisions.